Associations between chemoradiotherapy-based immune checkpoint blockade and posttreatment depression and anxiety in head and neck cancer patients: a cross-sectional study - Zhang, Yang; Chen, Yunhao; Zhang, Xianxing; Hong, Yafang; Zhou, Zihan; Ding, Xingchen (Frontiers in Immunology, 2025)
Immune checkpoint blockade (ICB) and combination treatment paradigms have gradually improved the prognosis of head and neck cancer (HNC) patients. However, HNC survivors struggle with anxiety and depression because of the large variety of persistent cancer-related or treatment-related symptoms. Recent studies have suggested that emotional distress is closely related to the therapeutic efficacy of ICB. In this study, 232 advanced HNC patients were recruited and their anxiety and depression status were assessed by the Hospital Anxiety and Depression Scale (HADS). Propensity score matching (PSM) was applied to balance confounders. The nearest-neighbor matching method was used for PSM matching to perform 1:1 matching. By comparing the anxiety and depression status of HNC patients after PSM, we showed that HNC patients receiving chemoradiotherapy (CRT) combined with ICB, both concurrent radiotherapy (RT) and sequential RT, had lower depression levels than did those receiving CRT alone. These findings suggest that ICB treatment may be associated with emotional status, which may could offer insights into ameliorate quality of life, both physically and psychologically, of HNC patients.